Sosialisasi Kompetensi Guru Madrasah MIN 3 Langkat di Era Revolusi Industri 5.0 - Ahmad Fuadi; Diani Syahfitri; Fitri Ramadani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This community service program aims to enhance the technological competencies of madrasah teachers in facing the challenges of the Industrial Revolution 5.0. The primary issue identified was the low level of technological skills among madrasah teachers, which can hinder the integration of technology into the learning process. To address this issue, a series of intensive training, continuous mentoring, and the formation of practitioner communities were implemented. The methods used included an initial survey to identify needs, intensive training followed by interactive workshops, and mentoring through reflective sessions and technical support. Active participation from teachers and community involvement in this process were key factors in the program's success. The results of this program showed a significant increase in teachers' technological skills, the formation of an active practitioner community, and positive social changes, including the emergence of local leaders among the teachers. The program also succeeded in creating new awareness regarding the importance of technology in education in the digital era. These findings support theories of technology-based learning and social change.